Combined oral contraceptives as a treatment method for female patients of reproductive age with heavy menstrual bleeding - E.I. Manukhina; I.R. Safaryan; M.A. Ovakimyan (LCC «Medicine-Inform», 2023)
I.B. Manukhin, E.I. Manukhina, I.R. Safaryan, M.A. Ovakimyan A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow, Russian Federation Background: heavy menstrual bleeding (HMB) is one of the unsolved problems in gynecological practice. The frequency of HMB is exactly unknown, which can be most likely related to an individually perceived blood loss volume. Patients with HMB are at high risk of iron deficiency and anemia. The main problem remains the lack of a single treatment algorithm for the HMB in female patients of reproductive age. Medical specialists should actively and, at the same time, effectively solve this clinical problem. Aim: to evaluate the efficacy of combined oral contraceptive (COC) containing 0.03 mg of ethinylestradiol and 2 mg of chlormadinone acetate in patients of reproductive age with HMB. Patients and Methods: the study involved 87 female patients aged 22-43 y.o. with complaints of HMB. After a complete clinical and laboratory examination, all patients were prescribed COC (0.03 mg ethinylestradiol and 2 mg chlormadinone acetate) for 6 months with subsequent efficacy evaluation. The following parameters were evaluated: menstruation duration, RBC, hemoglobin and ferritin count. Results: initially, hemoglobin count was 78.4±0.5 g /L, RBC count - 2.9×1012/L, and ferritin count - less than 29 mg/dL in the setting of normal hemoglobin count were observed in 31 (35.6%) female patients. COCs prescription demonstrated efficacy in blood loss volume decrease during menstruation, which was noted by 85 (97.7%) female patients. Thus, it contributed to the iron content normalization in 29 (93.5%) of 31 patients. The frequency of side effects, which were manifested by discomfort in the mammary glands, nausea, headache, did not exceed 17%. All manifestations associated with drug intake did not require its cancellation or additional treatment. Conclusion: COC containing 0.03 mg of ethinylestradiol and 2 mg of chlormadinone acetate is an effective drug for the treatment of HMB in female patients of reproductive age, allowing to reduce the frequency of latent iron deficiency forms. Keywords: combined oral contraceptives, heavy menstrual bleeding, ethinylestradiol, chlormadinone acetate, iron deficiency anemia, menstrual cycle control, hormonal contraception. For citation: Manukhin I.B., Manukhina E.I., Safaryan I.R., Ovakimyan M.A. Combined oral contraceptives as a treatment method for female patients of reproductive age with heavy menstrual bleeding. Russian Journal of Woman and Child Health. 2023;6(3):253-257 (in Russ.). DOI: 10.32364/2618-8430-2023-6-3-6.